Aceh's special autonomy in the perspective of asymmetric decentralization policies - Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This paper aims to reveal the implementation of autonomy in Aceh by using descriptive research methods through literature review. Based on the analysis of the literature sources, it can be found that the policy of regulation and division of territory as well as the pattern of relations between the Central Government and Regional Governments at the beginning of independence were pragmatic and tended to generalize, this could lead to armed conflicts such as in Aceh. Thus, an asymmetric decentralization policy is needed so that it can meet the demands of the Acehnese people, which historically, geographically, and socio-religiously have their own uniqueness and have made a major contribution to the struggle to achieve and maintain Indonesian independence.